Collaborative Governance In Mining Excavation: A Case Study Of Former Illegal Tin Mining In Bangka Regency - Hendrik, Hendrik; Alfitri, Alfitri; saptawan, Ardiyan; Nengyanti, Nengyanti (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2017)
Tin mining in Bangka has long been a source of livelihood for the community. However, the rampant illegal tin mining causes damage to the environment and ecosystems, as well as social conflicts. Collaborative governance, or collaborative governance, offers an alternative approach to more sustainable and equitable post-mine management. This study aims to analyze collaborative governance practices in the management of illegal tin mining in Bangka Regency. Through a case study in Perlang Village, Lubuk Besar District, this study examines how local stakeholders, such as local governments, communities, and business actors, work together in rehabilitating and revitalizing former tin quarries. The results of the study show that collaborative governance in Perlang Village has had a positive impact, namely the creation of active community participation in the decision-making process related to the management of former tin mines and increasing public awareness about environmental sustainability and sustainable management of natural resources. The findings of this study contribute to the understanding of collaborative governance practices in post-mining management in Indonesia. The recommendations of this study can help local governments and other stakeholders in implementing collaborative governance effectively to achieve post-mining management.